TRANSFORMASI RUANG DAN NILAI LAHAN: STUDI KASUS KORIDOR JALAN H. M. YASIN LIMPO, GOWA - Handayani, Risma; Usman, Khairul Sani; Nurul, Andini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
The H. M. Yasin Limpo Street corridor in Gowa Regency is experiencing increasingly dense and uncontrolled development, indicating a mismatch with the Regional Spatial Plan (RTRW). This situation threatens to degrade urban spatial quality, reduce comfort and safety, and hinder the realization of sustainable urban environments. The rapid and extensive land use changes in this area highlight the need for an in-depth study of the relationship between rising land values and land use transformation. This study aims to analyze the influence of land value on land use change within the corridor. A descriptive quantitative approach was used, employing overlay analysis, time series analysis, and comparative techniques to identify and assess land use dynamics over the past five years. The results show a 76.3% (1.32 ha) increase in commercial and service land, a 20.4% (1.27 ha) decrease in open land, and a 37.9% (1.27 ha) increase in built-up areas. Land value rose by 14.1%, from IDR 3,900,000/m² to IDR 4,450,000/m², contributing to a 32.67% intensification in land use change, predominantly toward commercial and service functions.